STUDENTS ATTITUDES AND PERCEPTIONS TOWARDS PEOPLE WITH DISABILITY - Dara Febriana (Idea Nursing Journal, 2013)
The aim of this study was to explore and interpret student perceptions and attitudes towardsdisability, factors underpinning the attitudes, and studentviews on discrimination and legal rights of disabledpeople. Students describe disability as being physically and mentally different that hinders them to dosomething. Findings from the review of literature indicated that developing an understanding of theattitudesthat predominate in a community, in turns would influence the action of its member. Therefore the way thestudents view the disabled will influence the student’s action towards the disabled. An explorative,interpretative design wasemployed. The data were collected by means of in-depth interviews with a sampleof students studying in one of university in Aceh, and were analyzed using content analysisapproach .Thefindings revealed five main themes emerged from the interview; definition of disability,differenttypes of disability, view towards disability, reason behind people behavior and discrimination.Thisstudy indicates that the attitude and perception towards people with disability appears to be affected by theyprevious encounter with people with disability and other factor thatunderpinning they viewed includedenvironment, situation, awareness and experience.Keyword : student, attitudes, perceptions, disability